2023
DOI: 10.1371/journal.pone.0271825
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of healthcare workers and volunteers training on improving tuberculosis case detection: A systematic review and meta-analysis

Abstract: Introduction Tuberculosis is the second most common infectious cause of death globally. Low TB case detection remains a major challenge to achieve the global End TB targets. This systematic review and meta-analysis aimed to determine whether training of health professionals and volunteers increase TB case detection. Methods We performed a systematic review and meta-analysis of randomized control trials and non-randomized control trials reporting on the effectiveness of health professionals and volunteers tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 30 publications
0
5
0
1
Order By: Relevance
“…The meta-analysis by Amare et al . of nine intervention trials demonstrated that training interventions improve the ability of providers to diagnose TB, significantly increasing the number of bacteriologically confirmed cases [ 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…The meta-analysis by Amare et al . of nine intervention trials demonstrated that training interventions improve the ability of providers to diagnose TB, significantly increasing the number of bacteriologically confirmed cases [ 60 ].…”
Section: Resultsmentioning
confidence: 99%
“… 24 Therefore, continuous training and support of local staff are necessary to increase tuberculosis diagnosis and encourage the initiation of preventive treatment in high-risk groups. 25 …”
Section: Discussionmentioning
confidence: 99%
“…The international literature reinforces the importance of better training professionals to properly detect and treat TB, revealing that using technologies in training activities can facilitate professional learning (24)(25)(26)(27)(28) . This has a relevant impact on health care quality, optimizing costs and time investment, in addition to contributing to expanding case detection and achieving the global goals of the End TB Strategy (29) .…”
Section: Introductionmentioning
confidence: 98%